Production of Palm-Based Esteramine Through Heterogeneous Catalysis - Aziz, H.A.; Aroua, M.K.; Yusoff, R.; Abas, N.A.; Idris, Z.; Hassan, H.A. (Springer Verlag (Germany), 2016)
This study involved maximizing the conversion of palm-based methyl palmitate to esteramine, an intermediate for esterquats via transesterification with triethanolamine, aided by Ca-Al as a heterogeneous catalyst in a 500-ml reaction unit. The effect of process parameters on the conversion was investigated. The optimum process parameters, consisting of a mole ratio of 1.8:1 (methyl palmitate:triethanolamine), 170 °C, 10 mbar, 0.5 % catalyst and a duration of 2 h, produced more than 90 % conversion. Transesterification employing Ca-Al is more environmentally friendly than the conventional approach using sodium methoxide, simplifies the downstream separation process and the reusability of the catalyst was successfully tested in three subsequent cycles.